A multifunctional α-Fe2O3@PEDOT core–shell nanoplatform for gene and photothermal combination anticancer therapy. Issue 9 (21st February 2022) - Odda, Atheer Hameid; Cheang, Tuck-Yun; Alesary, Hasan F.; Liu, Lirong; Qian, Xiaojun; Ullah, Naseeb; Wang, Gang; Pan, Yueyin; Xu, An-Wu
Abstract : A highly specific design and synthesis of an α-Fe2 O3 @PEDOT core–shell nanoplatform for multifunctional gene/photothermal combination anti-cancer therapy. Abstract : Exploration of versatile nanoplatforms within one single nanostructure for multidisciplinary treatment modalities, especially achieving a synergistic therapeutic efficacy of combinational gene/photothermal cancer therapy is still a great challenge in biomedicine and nanotechnology. In this study, a unique photothermal nanocarrier has successfully been designed and developed for a combination of gene therapy (GT) and photothermal therapy (PTT) of cancer cells. Surface-engineered iron oxides (α-Fe2 O3 ) nanoparticles (NPs) with poly(3, 4-ethylenedioxythiophene) (PEDOT) polymer coatings are synthesized using a one-pot in situ oxidative polymerization method. The results show that the as-prepared α-Fe2 O3 @PEDOT core–shell NPs with a uniform particle size exhibit positively charged surfaces, facilitating efficient siRNA Bcl-2 (B-cell lymphoma-2) uptake for delivery to breast cancer cells. More importantly, α-Fe2 O3 @PEDOT core–shell NPs not only display good biocompatibility and water dispersibility but also strong optical absorption enhancement in the Vis-NIR region as compared to α-Fe2 O3 NPs. The obtained α-Fe2 O3 @PEDOT core–shell NPs show an efficient photothermal conversion efficacy ( η = 54.3%) and photostability under NIR laser irradiation. As a result, both in vitro and in vivo biological studies on two types of breast cancer cells/tumors treated with α-Fe2 O3 @PEDOT-siRNA nanocomplexes demonstrate high cancer cell apoptosis and tumor inhibition induced by synergistic GT/PTT therapy under mild conditions compared to an individual GT or PTT alone. Taken together, this is the first example of the use of an α-Fe2 O3 @PEDOT core–shell nanoagent as a siRNA delivery nanocarrier for highly effective gene/photothermal combination anticancer therapy.